The European Arrest Warrant According to the Latest Changes and Additions - Ion Rusu (EIRP Proceedings, 2010)
Based on a dysfunction detected during the surrender of a pursued person under the European Convention on Extradition, the European Union instituted a new procedure that is the European arrestwarrant. Because initially the provisions of the Framework Decision 2002/584/JHA did not provide clear legal rules regarding which procedure to follow if the wanted person was not present at the trial, this situation was observed also by the European Court of Human Rights, it was amended and supplemented accordinglyby adopting the Framework Decision 2009/299/JAI. The evaluation of the provisions of both acts highlights the existence of some incomplete legal rules, which in time they will cause some dysfunctions regarding the issuing and the enforcement of a European arrest warrant. We also consider modifying and expanding thelegal rules relating to mandatory and optional reasons for the refusal of enforcement of a European arrest warrant, and the inclusion of educational deprivation of liberty measures in the category of the reasons that justify the request of the execution of a European arrest warrant. The originality of the work results from the analysis of the recent changes of the European legislative framework document and the critical opinions expressed about some stipulations, which in our opinion are incomplete. The paper can be useful not only for the Romanian legislator, but also for the European one, from the perspective of modifying the concerned legalacts and also the doctrine. It has a major importance in this domain for ensuring an area of freedom, security and justice in the European Union.